Can human capital theory explain why nurses are so poorly paid? - Nowak, Margaret; Preston, Alison (Curtin University of Technology, 2000)
This paper uses Australian Census data to examine the earnings of femaleprofessionals. Comparisons are made between Registered Nurses (RNs),Teachers, Social Professionals, Health Professionals and BusinessProfessionals. Wage decompositions show that RNs earn significantly less thanother female Professionals and that the observed differentials cannot beexplained by differences in human capital endowments. The evidence presentedis strongly suggestive of monopsonist or oligopsonist power in the setting ofnurse wages ? with a manifestation being persistent labour marketdisequilibrium. Changing the relative reward structure for nurses may helpaddress the on-going nursing ?shortage? in Australia, although further researchin this area is called for.